Development Of Electrospun Nanofibres Containing Ibuprofen Grafted Nanocrystalline Cellulose For Dermal Delivery - Ahmed Al-Mashhadani, Abdulsalam Qahtan (2022)
Nanomaterials offer various benefits in dermal drug delivery, including a large surface-to-volume ratio and enhanced drug disposition in the skin. Nanocrystalline cellulose (NCC) is a potential drug nanocarrier due to its abundant surface hydroxyl groups, making it suitable to be grafted with active pharmaceutical ingredients. However, dermal delivery of nanomaterials needs a proper platform to ensure a good distribution in the formulations. The objective of the thesis is to investigate the electrospun nanofibres carrying ibuprofen-grafted NCC for dermal delivery system application. Firstly, NCC was isolated from kapok pulp using multiple acid hydrolysis with the assistance of central composite design to optimise the reaction conditions, namely acid concentration, reaction temperature and time. At the optimum condition, NCC produced showed a rod-like shape with a length of 230.3 ± 39.8 nm, zeta potential of -39.7 ± 0.6 mV, yield of 18.8 ± 1.5% and crystallinity index of 72.6%.